Relações entre as estratégias de construção da competência lexical e a compreensão leitora: a prova Brasil de língua portuguesa - Polli, Vanessa (2014)
Given the growing importance attributed to the evaluations of basic education on the international scenario and on Brazilian scenario – ENEM, SAEB, PISA, Prova Brasil, Provinha Brasil - and the relation of those tests with reading, this work aims to study the construction process and evaluation of reading competence in Prova Brasil of Portuguese Language, in primary education, in order to know which aspects are valued, particularly in relation to the construction of lexical competence, since restrictions around that competence may ultimately compromise the comprehension. Considering the complexity of the lexicon acquisition process, we see that the learning of most words occurs in situations of language use through indirect instruction. However, even agreeing that a systematic teaching is able to increase the quality of the knowledge of words, we believe that the greater emphasis should be on developing strategies to learn the lexicon (context clues, morphological clues and dictionary), that associated with prior knowledge of the reader, favor the reading comprehension and allow the formation of a more independent learner. In order to make such strategies more effective, it is necessary that the student develops a metacognitive behavior, i.e., they can assume a monitoring attitude related to their own learning. From these theoretical considerations, we analyze the proposal of the guiding documents of Prova Brasil (National Curriculum Parameters and Reference Matrices – a free translation to Parâmetros Curriculares Nacionais e Matrizes de Referência) concerning aspects related to lexical competence as a support for reading comprehension. Then, using quantitative and qualitative criteria, we analyze the proposed items for Prova Brasil (fifth and ninth grades) available on INEP website in order to investigate what the importance attributed to lexical competence is, as well as if the use of some kind of lexical teaching strategy for the resolution of the item, even if indirectly, is expected. Finally, observing aspects related to lexical competence, we undertook a comparative analysis between what is shown by the documents that support Prova Brasil and what actually happens in the formulation of the items of the test. With this research, we seek to highlight the importance of lexical knowledge for reading comprehension, the reason why we can say that lexical knowledge is complex, and how we can use this knowledge as a foundation to the reading comprehension.